Alternative Solution for Failed Harvest Effected of Dry Season at “Jeruk Keprok 55 Kota Batu” Productivity through Sprinkle Irrigation Construction - Bambang Suharto; Liliya Dewi Susanawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
Batu-Malang Government area is one of central production of orange fruit production in East Java. At dry season, the orange plant produce low production level, because there is no available enough water inside the soil. From this facts, it needs effort to increase the orange production especially to facing the dry season, through a new technology engineering and construction of sprinkle irrigation system to increase orange production especially at dry season. Average of irrigation water necessary per days at the treatment of water shower period indicated that the treatment of four times a week reach 20,202 liter as highest value and the treatment of once a week reach 13,000 liter as lowest value. At the bud crown not found obvious differences between factors with the treatment of T1R3 have highest inclination with 175 number of flowers. The treatment of T1R3 indicated 359.667 as highest result and T4R3 indicated 233.667 as lowest result. The treatment of T1R3 indicated 658 as highest result and the control treatment indicated 426.333 as lowest result. The treatment of T1R3 produced 1032.667 as highest result and the control treatment produced 404 as lowest result.